The Relationship Between Gensini Score and In-Hospital Mortality in Patients with ST-Segment Elevation Myocardial Infarction - Yildirim,Erkan (2017)
Abstract Background: To date, several validated patient-based risk scores have been established to predict mortality and morbidity in patients presenting with ST-segment elevation myocardial infarction (STEMI). The Gensini score was originally developed to quantify the severity of coronary artery disease (CAD). Objectives: We intend to assess the association between severity of CAD assessed by Gensini score and in-hospital mortality in patients with STEMI undergoing primary percutaneous coronary intervention (P-PCI). Methods: A total of 539 patients presenting with acute STEMI, who underwent P-PCI within the first 12 hours from the onset of symptoms, were included. The severity of CAD was expressed as the sum of the Gensini scores for each lesion. Patients' demographic variables, medical histories and clinical features, as well as in hospital major adverse events were obtained from the medical reports. Results: Of these 539 patients, 416 (77.2%) were male and mean age was 59.14 ± 12.68 years. In-hospital mortality rate was 5.4% (29 patients; 16 men). Mortality rate was 10.5% in female patients and 3.8% in males (P = 0.004). Mean Gensini scores were significantly different in the comparison between patients who survived (54.54 ± 26.34) and those who died (80.17 ± 26.51) (P = 0.001). The multivariable Cox proportional hazards regression analysis model revealed that the Gensini score (P = 0.037), female gender (P = 0.039), serum urea levels (P = 0.041), uric acid levels (P = 0.008) and LVEF (P = 0.001) were independently associated with in-hospital mortality in patients with STEMI undergoing P-PCI. Conclusion: The Gensini score is independently associated with in-hospital mortality in STEMI patients treated with P-PCI. Therefore, it might play an important role in risk stratification of STEMI patients.